FT-IR and Micro-Raman Spectroscopic Studies of Archaeological Potteries Recently Excavated in Tamilnadu, India - K. Prabakaran1, A. Mohamed Musthafa1 and R. Hemamalini2, G. Velraj1*, (Recent Research in Science and Technology, 2010)
The spectroscopic techniques represent one of the most powerful tools to investigate the structure of all the materials and chemical composition of the cultural object like potteries and ceramic. The spectroscopic techniques that are used in the present study are FT-IR absorption and Micro Raman spectroscopy. The technique of Raman spectroscopy was used to examine the composition of ancient potteries. Normal dispersive Micro-Raman spectroscopy is found to be the most effective analytical technique in the study. The potteries maintain aesthetic characteristics so that this type of artifacts can be considered very specific trace of every civilization. Therefore it is of great importance to acquire knowledge about the chemical composition in the clay of archaeological artifacts. In the present study potteries are excavated in Salamankuppam, Tamilnadu, India subjected to record the mid IR in the range 4000–400 cm-1 and the Micro Raman range of 1800 – 100 cm-1. The clay mineral present in the pottery samples are identified through FT-IR method and was confirmed with Raman Spectroscopy, since the IR and Raman Spectroscopy are complement to each other. The major primary minerals present in the samples are Kaolinite and the secondary mineral present is quartz and the accessory minerals present in the samples are hematite, magnetite and feldspar.